Latinidad at the crossroads : insights into Latinx identity in the twenty-first century - Gerke, Amanda Ellen; González Rodríguez, Luisa María (Critical approaches to ethnic American literature, 2021)
In Latinidad at the Crossroad: Insights into Latinx identity in the Twenty-First Century Gerke and González Rodríguez provide flashing glimpses into the ways in which Latinas/os struggle to forge their multiracial and multicultural identities within their own communities and in mainstream U.S. society. This volume encompasses an interdisciplinary perspective on the complex range of latinidades that confronts stereotypical connotations, and simultaneously advocates a more flexible (re)definition that may overcome static collective representations of identity, ethnicity and belonging. Well-positioned in the current political context, the notion of latinidad is examined as a complex sociological phenomenon of identity-construction which is affected by outside influences and is used as a powerful linguistic, cultural and ideological weapon to denounce oppression and deconstruct stereotypes. Including chapters from foundational and influential scholars, this collection moves towards a dynamic exploration of how Latinx are remapping their identity positions in twenty-first century America. Contributors: Francisco A. Lomelí, José Antonio Gurpegui, Esther Álvarez López, Ylce Irizarry, Luisa María González Rodríguez, Ewa Antoszek, Fernando Aquino.